Belajar Berfilsafat Melalui Lirik Tembang - Suwartono Suwartono (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
In this paper song lyrics are seen as a literary work. They are identical in nature to poems. However, to most of us, song lyrics are more familiar than poems. This paper argues that by appreciating songs (lyrics) one’s philosophical power becomes trained. Its content, that is quite often rich in hermeneutics (related to interpretation), semiotics (related to symbols) and esthetics (related to arts, beauty) – some of the approaches to philosophy, might be responsible for this. For illustrations, four selected, analysed song lyrics have been presented here.